Biomarkers of nucleic acid oxidation - A summary state-of-the-art - Chao, Mu-Rong; Evans, Mark D; Hu, Chiung-Wen; Ji, Yunhee; Møller, Peter; Rossner, Pavel; Cooke, Marcus S (Redox biology, 2021)
Oxidatively generated damage to DNA has been implicated in the pathogenesis of a wide variety of diseases. Increasingly, interest is also focusing upon the effects of damage to the other nucleic acids, RNA and the (2'-deoxy-)ribonucleotide pools, and evidence is growing that these too may have an important role in disease. LC-MS/MS has the ability to provide absolute quantification of specific biomarkers, such as 8-oxo-7,8-dihydro-2'-deoxyGuo (8-oxodG), in both nuclear and mitochondrial DNA, and 8-oxoGuo in RNA. However, significant quantities of tissue are needed, limiting its use in human biomonitoring studies. In contrast, the comet assay requires much less material, and as little as 5 μL of blood may be used, offering a minimally invasive means of assessing oxidative stress in vivo, but this is restricted to nuclear DNA damage only. Urine is an ideal matrix in which to non-invasively study nucleic acid-derived biomarkers of oxidative stress, and considerable progress has been made towards robustly validating these measurements, not least through the efforts of the European Standards Committee on Urinary (DNA) Lesion Analysis. For urine, LC-MS/MS is considered the gold standard approach, and although there have been improvements to the ELISA methodology, this is largely limited to 8-oxodG. Emerging DNA adductomics approaches, which either comprehensively assess the totality of adducts in DNA, or map DNA damage across the nuclear and mitochondrial genomes, offer the potential to considerably advance our understanding of the mechanistic role of oxidatively damaged nucleic acids in disease.
Keywords: oxidační stres; Chromatography, Liquid; poškození DNA; 8-Hydroxy-2'-Deoxyguanosine; biologické markery; Oxidative stress; DNA Damage; Biomarkers; nukleové kyseliny; tandemová hmotnostní spektrometrie; DNA repair; chromatografie kapalinová; deoxyguanosin; Nucleotide pool; lidé; RNA; Humans; DNA; Nucleic Acids; Tandem Mass Spectrometry; Oxidative Stress; 8-hydroxy-2'-deoxyguanosin; Deoxyguanosine